Grain Yield, Nutrient Accumulation and Fertilizer Efficiency in Bread Wheat under Variable Nitrogen and Phosphorus Regimes - Muhammad Irfan; Muhammad Abbas; Javiad Ahmed Shah; Muhammad Yousuf Memon (Journal of Basic & Applied Sciences, 2018)
Balanced crop nutrition is one of the important tools necessary for sustaining crop productivity, maintaining soil fertility and ensuring food security worldwide. Nitrogen and phosphorus are essential plant macronutrients, nevertheless, most of the Pakistani soils exhibit moderate to severe deficiency of these nutrients. Furthermore, considerable genetic variations exist among wheat genotypes for nutrient acquisition and utilization which illustrate their differential nutrient requirements to produce higher yields. A field experiment was conducted in order to formulate balanced fertilizer recommendations for newly evolved wheat genotype SD-998 to achieve maximum yield potential. Ten treatments viz., 0-0 (control), 90-23, 90-45, 90-70, 120-30, 120-60, 120-90, 150-40, 150-75 and 150-110 kg N-P2O5 ha-1 were applied according to randomized complete block design with three replications. Analysis of variance revealed that growth, yield and yield related attributes as well as nutrient accumulation were significantly (P ? 0.05) influenced by varying N and P rates. The maximum plant height (100.8 cm), number of tillers per plant (10), spike length (10.3 cm), number of grains per spike (66), 100-grain weight (4.10 g) and grain yield (4990 kg ha-1) was recorded in treatment having 150-110 kg N-P2O5 ha-1. The highest P recovery efficiency (20.8 %), agronomic N efficiency (19.4 kg kg-1) and agronomic P efficiency (36.8 kg kg-1) were attained at 120-30, 90-70 and 150-40 kg N-P2O5 ha-1, respectively. However, the highest total N accumulation (140.8 kg ha-1), P accumulation (21.0 kg ha-1), N recovery efficiency (71.1 %) and profit (Rs. 73625 ha-1) were noticed at 150 kg N plus 110 kg P2O5 ha-1. Thus, 150-110 kg N-P2O5 ha-1 (N:P2O5 in 4:3 ratio) was suggested as the most balanced and economical dose for the tested wheat genotype.